determine a solução da equação de 2° grau (-x2)+27x-4
Soluções para a tarefa
Respondido por
1
a = 1
b = 27
c = -4
fórmulas:
Δ = b²-4ac
X1 = (-b + √Δ) / 2a
X2 = (-b - √Δ) / 2a
cálculo:
Δ = b²-4ac
Δ = 27² - 4*1*(-4)
Δ = 729 + 16
Δ = 745
X1 = (-b + √Δ) / 2a
X1 = (-27 + √745) / 2*1
X1 = (-27 + 27,29) / 2
X1 = (0,29) / 2
X1 = 0,147
X2 = (-b - √Δ) / 2a
X2 = (-27 - √745) / 2*1
X2 = (-27 - 27,29) / 2
X2 = (54,29) / 2
X2 = 27,147
b = 27
c = -4
fórmulas:
Δ = b²-4ac
X1 = (-b + √Δ) / 2a
X2 = (-b - √Δ) / 2a
cálculo:
Δ = b²-4ac
Δ = 27² - 4*1*(-4)
Δ = 729 + 16
Δ = 745
X1 = (-b + √Δ) / 2a
X1 = (-27 + √745) / 2*1
X1 = (-27 + 27,29) / 2
X1 = (0,29) / 2
X1 = 0,147
X2 = (-b - √Δ) / 2a
X2 = (-27 - √745) / 2*1
X2 = (-27 - 27,29) / 2
X2 = (54,29) / 2
X2 = 27,147
Perguntas interessantes
Matemática,
9 meses atrás
História,
9 meses atrás
ENEM,
9 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás